Islamic performance index and profitability with the moderating role of intellectual capital in Indonesian Islamic banks - Rita, Stella Dewi; Sugiarti, Dian (Economics, Finance, and Business Review, 2025)
This study analyzes the influence of the Islamic Performance Index (IPI) and Intellectual Capital (IBVAIC) on profitability (Return on Assets), as well as the moderating role of IBVAIC, at 10 Islamic Commercial Banks (ICBs) in Indonesia from 2019 to 2024. Using a quantitative approach with a Common Effects Model (CEM), the results show that the independent variables collectively have a significant effect on the dependent variable. An R-squared value of 0.5610 indicates that the model explains 56.10% of the variation in the dependent variable. Partially, the Profit Sharing Ratio and Equitable Distribution Ratio show a significant negative influence. The study also finds that IBVAIC significantly moderates the relationship between all IPI indicators and profitability. This moderation is negative for the Profit Sharing, Zakat Performance, and Equitable Distribution ratios, but positive for the Islamic Income vs. Non-Islamic Income ratio. The findings highlight the complex interplay between Sharia compliance, intellectual capital, and financial performance. This study has significant policy implications, suggesting that bank management and regulators must strategically align intellectual capital management with Sharia principles to optimize profitability.